Arginase and nitric oxide - Murray, Peter (Henry Stewart Talks, 2009)
Catabolism of arginine to downstream substrates, Catabolism of arginine in macrophages, Nitric oxide production, Control of iNOS at the transcriptional level, Role of nitric oxide in immunity to intracellular pathogens with a focus on mycobacterial disease, Structure of arginases, Transcriptional control of arginase 1 in the liver vs. macrophages, Arginases can suppress nitric oxide production by substrate depletion, Pathogens use many mechanisms to regulate nitric oxide, Arginases and alternatively-activated macrophages (AAMs), Schistosome infection as an example of AAM function, AAMs and arginases, Arginase inhibition by small molecules, Outstanding questions
Updated at 2011/08/31